Müller glial cells induce stem cell properties in retinal progenitors in vitro and promote their further differentiation into photoreceptors - Simon, Maria Victoria (2012)
Using stem cells to replace lost neurons is a promising strategy for treating retinal neurodegenerative diseases. Among their multiple functions, Müller glial cells are retina stem cells, with a robust regenerative potential in lower vertebrates, which is much more restricted in mammals. In rodents, most retina progenitors exit the cell cycle immediately after birth, differentiate as neurons, and then cannot reenter the cell cycle. Here we demonstrate that, in mixed cultures with Müller glial cells, rat retina progenitor cells expressed stem cell properties, maintained their proliferative potential, and were able to preserve these properties and remain mitotically active after several consecutive passages. Notably, these progenitors retained the capacity to differentiate as photoreceptors, even after successive reseedings. Müller glial cells markedly stimulated differentiation of retina progenitors; these cells initially expressed Crx and then developed as mature photoreceptors that expressed characteristic markers, such as opsin and peripherin. Moreover, they were light responsive, insofar as they decreased their cGMP levels when exposed to light, and they also showed high-affinity glutamate uptake, a characteristic of mature photoreceptors. Our present findings indicate that, in addition to giving rise to new photoreceptors, Muller glial cells might instruct a pool of undifferentiated cells to develop and preserve stem cell characteristics, even after successive reseedings, and then stimulate their differentiation as functional photoreceptors. This complementary mechanism might contribute to enlarge the limited regenerative capacity of mammalian Müller cells.